Experimental Investigation And Numerical Simulation Of Ohmic Heating For Liquid Food Pasteurization Under Laminar Condition - Salih Elfakie, Elzubier Ahmed (2008)

(untitled)
Pasteurization of liquid food - guava juice and soymilk by continuous ohmic heating within a temperature range of 30-90 0C, was performed in a 3-D non – axisymmetric ohmic heater. (Three stripe electrodes positioned along the walls and oriented 1200 to the axis of the pipe), using 3-phase 50-60 Hz alternative voltages, with Delta connection. A mathematical model describing the flow and thermal behavior of guava juice and soymilk solution in a continuous ohmic heating unit was developed. The equations for conservation of mass, momentum and energy and electric field distributions including temperature dependent electrical conductivities, thermo physical and rheological properties were solved using a commercial Computational Fluid Dynamics (CFD) software package (FLUENT 6.1) which was based on finite volume method of analysis. User defined functions (UDF’s)employed in the original platform (FLUENT 6.1), were used for the solution of scalar equations - electrical field model. Thermo-physical and rheological properties of soymilk and guava juice were measured. Soymilk was found to be Newtonian and guava juice a Non Newtonian (power law n = 0.0.5978 and k = 0.117 Pa sn). Measurements of electrical conductivities at various temperatures for guava juice and soymilk were carried out. These properties were then used as inputs for the CFD modelling. The numerical calculation results have provided reasonable information for optimizing the design of ohmic heating cell geometry to improve the uniformity of the electrical and thermal fields across the heating cell in order to avoid over and under-processing of liquid foods. The heating rate of soymilk was found to be higher than that of guava juice. The current density of both guava juice and soymilk was found to exceed the critical value. However, experimentally the soymilk, a protein solution, was found to rapidly deposit on the surface of the electrodes. No ohmic heating was conducted thereafter with the soymilk. Temperature, flow pattern, electrical field distribution and the slowest heating zone (SHZ) during ohmic heating of both liquid foods (3D) were predicted. Experimental and simulated temperatures were in good agreement at different locations along the ohmic heating axis for guava juice, thus validating the CFD model and simulation. The pasteurization calculations were done for guava juice (3.8 0brix) and soymilk (7.8±0.02 0brix) using the pathline of the highest velocity simulated from the CFD, and pasteurisation was adequately and rapidly achieved.